Pengaruh Motivasi Kerja terhadap Produktivitas Karyawan pada PT. Salawati Motorindo Sorong - Meigi R. Salampessy; Andrey Maryen; Yanti Timisela (Departement of Mathematics Education, 2023)
This research is motivated by the frequent occurrence of employee turnover in a company or business organization which has an impact on work productivity in the company due to lack of work motivation and employee work discipline. Therefore, work productivity is very important to be applied to this company to achieve the goals that have been set. The purpose of this study is the effect of motivation on the work productivity of employees of PT. Salawati Motorindo Sorong. This study uses a descriptive method with a quantitative approach. data collection by questionnaire technique. Respondents in this study as many as 56 people who are employees at PT. Salawati Motorindo Sorong. Hypotheses were formulated and tested using simple linear regression analysis. The results showed that there was a positive effect of 0,189 and significantly less than 0,05 between work motivation on employee productivity. Meanwhile, for the correlation coefficient interval relationship, there is a value of 0,40 – 0,599 or a moderate level of correlation. Meanwhile, the coefficient of determination is 0.198 or 19.8% and 80.2% is influenced by other factors.